Early contributions to the theory of Islamic governance: ʿAbd al-Raḥmān al-Awzāʿī - Bouzenita, Anke Iman (Oxford University Press, 2012)
This paper deals with the political understanding of one of the early masters of fiqh, ʿAbd al-Raḥmān al-Awzāʿī (d. 157/773), as manifested in his biography and what can be substantiated of his legal scholarship. It argues that, although the principles of Islamic governance were systematically formulated and laid down by later generations, the corresponding concepts were well established and acted upon in the generation of this famous Syrian scholar. The paper draws on primary historical source material that has hitherto been largely underused. It sheds light on the scholar and his time, his evaluation of political events, his attitude to and relationship with people in power and his views on the legitimacy of rulers.